Former Social Democratic Partisanship, Working-Class Background, and Support for Right-Wing Populist Parties: A Research Note - Marc Debus; Richard Traunmüller (Politische Vierteljahresschrift, 2025)
Modern democracies have seen increasing support for populist parties in recent years. One major topic in this research area concerns the roles of individuals with a~working-class background and former supporters of social democratic parties in the increasing vote share of right-wing populist parties. In this research note, we study the determinants of support for the Alternative for Germany (AfD) in the 2013 and 2017 Bundestag (German federal) elections. Using data from the German Socio-Economic Panel, we show that individuals with a~working-class background were more likely to vote for the AfD than for other parties. However, former Social Democratic Party voters and identifiers who had a~working-class background were also more likely to support the radical right and anti-immigrant AfD in 2017 over other parties or over non-voting. We do not find similar effects for the 2013 Bundestag election, when the AfD adopted a~less extremist, Eurosceptic, and national-conservative profile. Our findings indicate that the German Social Democrats lost previous supporters with a~working-class background when a~radical right party with an anti-immigrant profile competed for votes. We discuss the implications of these findings for the stability of liberal democracies. – – In den modernen Demokratien ist die Unterstützung für populistische Parteien in den letzten Jahren gestiegen. Ein wichtiges Thema in diesem Forschungsbereich ist die Rolle von Personen aus der Berufsgruppe der Arbeiter und ehemaliger Anhänger sozialdemokratischer Parteien für den steigenden Stimmenanteil rechtspopulistischer Parteien. In diesem Beitrag untersuchen wir die Determinanten der Unterstützung für die ,,Alternative für Deutschland“ (AfD) bei den Bundestagswahlen 2013 und 2017. Anhand von Daten des sozioökonomischen Panels (GSOEP) zeigen wir, dass Arbeiter im Vergleich zu anderen Parteien und zur Option der Nichtwahl häufiger für die AfD stimmten. Ehemalige SPD-Wähler und Befragte mit früherer SPD-Parteiidentifikation, die einen Arbeiterhintergrund haben, unterstützten 2017 jedoch auch eher die rechtspopulistische und migrationsskeptische AfD als andere Parteien. Für die Bundestagswahl 2013, als die AfD ein weniger radikales, euroskeptisches und nationalkonservatives Profil annahm, finden wir keine ähnlichen Effekte. Unsere Ergebnisse deuten darauf hin, dass die deutschen Sozialdemokraten frühere Anhänger aus der Gruppe der Arbeiter verloren haben, als eine weit rechtsstehende Partei mit einem einwanderungsfeindlichen Profil um Stimmen warb. Wir diskutieren die Implikationen dieser Ergebnisse für die Stabilität liberaler Demokratien.
Keywords: 320; Working class; Social democracy; Voting behaviour; Voter migration; Right-wing populism; Germany; Arbeiter; Sozialdemokratie; Wahlverhalten; Wählerwanderung; Rechtspopulismus; Deutschland